Disentangling the associations between parental BMI and offspring body composition using the four‐component model. Issue 4 (5th February 2016) - Devakumar, Delan; Grijalva‐Eternod, Carlos; Cortina‐Borja, Mario; Williams, Jane; Fewtrell, Mary; Wells, Jonathan
ABSTRACT: Objectives: This study sets out to investigate the intergenerational associations between the body mass index (BMI) of parents and the body composition of their offspring. Methods: The cross‐sectional data were analyzed for 511 parent–offspring trios from London and south‐east England. The offspring were aged 5–21 years. Parental BMI was obtained by recall and offspring fat mass and lean mass were obtained using the four‐component model. Multivariable regression analysis, with multiple imputation for missing paternal values was used. Sensitivity analyses for levels of non‐paternity were conducted. Results: A positive association was seen between parental BMI and offspring BMI, fat mass index (FMI), and lean mass index (LMI). The mother's BMI was positively associated with the BMI, FMI, and LMI z ‐scores of both daughters and sons and of a similar magnitude for both sexes. The father's BMI showed similar associations to the mother's BMI, with his son's BMI, FMI, and LMI z ‐scores, but no association with his daughter. Sensitivity tests for non‐paternity showed that maternal coefficients remained greater than paternal coefficients throughout but there was no statistical difference at greater levels of non‐paternity. Conclusions: We found variable associations between parental BMI and offspring body composition. Associations were generally stronger for maternal than paternal BMI, and paternal associations appeared to differ between sons and daughters. In this cohort, the mother's BMI was statistically significantly associated with her child's body composition but the father's BMI was only associated with the body composition of his sons. Am. J. Hum. Biol. 28:524–533, 2016. © 2016 The Authors American Journal of Human Biology Published by Wiley Periodicals, Inc.